here's how to write the problem with your keyboard:
1) x+1= 9x^3 + 9x^2
2) x^3 = 4x
here's how to solve number 1:
x+1=9x^3 + 9x^2
put everything on the same side of the equal sign and set it to zero:
9x^3 + 9x^2 -x -1 = 0
factor the equation so you can solve the terms for x; first factor out the cube and then the quadratic:
(3x+1)(3x^2+2x+1) = 0
(3x+1)(3x+1)(x+1) = 0
notice how setting the equation to zero allows you to discover the possible values of x; here are the possible values of x in this equation:
3x+1 = 0; 3x = -1; x = -1/3
3x+1 = 0; 3x = -1; x = -1/3
x+1 = 0; x = -1
here's how to solve number 2:
x^3 = 4x
it's the same steps as problem one:
x^3 - 4x = 0
x(x^2 - 4) = 0
x(x-2)(x+2) = 0
these are the possible values of x in this equation:
x = 0
x-2 = 0; so x = 2
x+2 = 0; so x = -2
2006-09-09 16:09:52
·
answer #1
·
answered by ronw 4
·
0⤊
0⤋
1) You need to use the principles of synthetic division. First re-write this as
9x^3 + 9x^2 - x - 1 =0
Any rational root of this equation will be of the form a/b where a is a factor of the 0th term (1) and b is a factor of the nth term (9). This makes the possibilities +/- 1, +/- 1/3 and +/- 1/9. Let's try -1/3 or 3x+1. (Use synthetic division on scratch paper by computer...) Yep, that works. (3x+1)(3x^2+2x-1) is the same as above, so one solution is -1/3. Next factor 3x^2+2x-1 into (3x-1)(x+1). The last two answers are 1/3 and -1.
2) Rewrite to x^3 - 4x=0. Factor to x(x^2-4)=0 then to x(x-2)(x+2)=0. The solutions are 0, 2 and -2
2006-09-09 14:08:16
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
1) x= 1/3
2) x=2
2006-09-09 15:38:52
·
answer #3
·
answered by tschneuer 1
·
0⤊
0⤋
x+1= 9x^3+9x^2 ^ means exponents.
9x^3+9x^2-x-1=0 let Y=9x^3+9x^2-x-1
dY/dx=27x^2+18x-1, 27x^2+18x-1 is equal to zero when dY/dx is stationary. then d^2Y/dx^2= 27x+18
then
x= 1/3 and -1 when dY/dx is equal to zero. thus 1/3 and -1are minimum value and maximum value of this equation.
this problem can be solved by CALCULUS.
2) x^3=4x , x^2=4 ,thus x= +2 and -2
2006-09-09 15:59:16
·
answer #4
·
answered by free aung san su kyi forthwith 2
·
0⤊
0⤋
1) x = 1
2) x = 2
* for number 1, just keep on regrouping the similar variables, multiply each time to get rid of cube and spuares
2006-09-09 14:12:01
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
1. x = -1
(-1) + 1 = 9 * (-1)^3 + 9 * (-1)^2
-1 + 1 = -9 + 9
0 = 0
2. x = 2
x^3 = 4x
x^2 = 4
x=2
2006-09-09 14:18:54
·
answer #6
·
answered by TychaBrahe 7
·
0⤊
0⤋
2) x^3=4x
x^3 - 4x = 0
x (x^2 - 4) = 0
x=0 and x^2 - 4=0
x^2=4
x= + and - 2
2006-09-09 14:02:44
·
answer #7
·
answered by Lin 1
·
0⤊
0⤋
the answer for #2 is 2
2006-09-09 13:50:08
·
answer #8
·
answered by surfing ='s life 3
·
0⤊
0⤋
1)
oups ... sorry for the first answer, i'm french and i had think that the term 'square' means '4' ....
==========================
2)
x^3 = 4x
x^2 = 4
_________________
x = {-2 ; 2}
2006-09-09 13:57:39
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋
x=root4 (2) from second equation
then substitute root4 (2) into x in first equation
2006-09-09 13:50:39
·
answer #10
·
answered by Anonymous
·
0⤊
0⤋